The awareness of personal financial management among employees at Significant Technologies Sdn Bhd / Siti Nur Shahirah Azman - Azman, Siti Nur Shahirah (2014)
This paper investigates the awareness of personal financial management among employees at Significant Technologies Sdn Bhd. The problem statement in this research papers is the women have lower scores than men in the awareness of personal financial management because women in general are less interested in the topic of investment and Personal Finance. Other than that, women are also less the knowledge about the personal financial management will become the risk of bankruptcies, credit problems, poor savings rates. Nowadays, the personal financial management is important to avoid from the overspending, bankruptcy. So, I want to determine the factor that can influence the awareness of personal financial management among employees at Significant Technologies Sdn Bhd. The objectives of the study are to study the relationship between financial knowledge skills, income level and retirement planning with the awareness personal financial management. Furthermore, the research methodology is use to researcher to interpret data from questionnaire that has been distributed to respondents. Thus, 50 of questionnaires were disturbed to employees at Significant Technologies Sdn Bhd. The method use reliability statistic (Conbach’s Alpha), frequency (Demographic statistic), descriptive statistic and hypothesis testing which consist of Pearson coefficient matrix, crosstab and regression analysis. Besides that, I have found out knowledge skills and retirement planning has significant relationship with the awareness of personal financial management among employees at Significant Technologies Sdn Bhd. And also, I find out income level have no significant relationship with the awareness of personal financial management among employees at Significant Technologies Sdn Bhd.